2018
DOI: 10.26714/jk.7.1.2018.69-79
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Pengetahuan Dan Sikap Ibu Hamil Resiko Tinggi Dengan Penyuluhan Berbasis Media

Abstract: (P-value = 0,266), there is difference of attitude before counseling (Leaflet) with attitude after counseling (Leaflet) (p-value = 0,266). The conclusions of health education using LCD media and leaflets are instrumental in helping pregnant women get information about early detection of high risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
2
0
12
Order By: Relevance
“…By considering these two results, it can be concluded that the development of educational media in the form of leaflets had a positive effect in increasing pregnant women knowledge about complications of pregnancy and childbirth. This research was in line with research conducted by Indrawati et al [14] that there was a difference between the pre-counseling knowledge (leaflet) and post-counseling knowledge (leaflet) about increasing the knowledge of high-risk pregnant women with mediabased counseling (p = 0.000). Similar to the research conducted by Fitriani et al [10], it also showed that the average knowledge of pregnant women before and after being provided with health education about high-risk pregnancies in the experimental group showed p = 0.000.…”
Section: Discussionsupporting
confidence: 91%
“…By considering these two results, it can be concluded that the development of educational media in the form of leaflets had a positive effect in increasing pregnant women knowledge about complications of pregnancy and childbirth. This research was in line with research conducted by Indrawati et al [14] that there was a difference between the pre-counseling knowledge (leaflet) and post-counseling knowledge (leaflet) about increasing the knowledge of high-risk pregnant women with mediabased counseling (p = 0.000). Similar to the research conducted by Fitriani et al [10], it also showed that the average knowledge of pregnant women before and after being provided with health education about high-risk pregnancies in the experimental group showed p = 0.000.…”
Section: Discussionsupporting
confidence: 91%
“…Perlu adanya upaya promotif dan preventif sampai dengan waktunya diambil dengan sikap tegas dan cepat untuk menyelamatkan ibu dan janinnya. 6,7,8 Pada tabel 2 memperlihatkan yang memiliki komunikasi interpersional kurang dengan pengetahuan kurang sebanyak 43 responden (41,7%), hal ini terjadi karena kurangnya ibu hamil berkomunikasi dengan tetangga tentang cara mencegah kematian ibu pada ibu hamil risko tinggi dan komunikasi interpersional kurang dengan pengetahuan cukup sebanyak 30 responden (29,1%), hal ini terjadi karena kurangnya kumunikasi ibu hamil dengan keluarga (saudara/mertua/orang tua) tentang cara mencegah kematian ibu hamil risiko tinggi, sedangkan yang memiliki komunikasi interpersional baik dengan pengetahuan kurang sebanyak 7 responden (16,8%), hal ini terjadi karena ibu hamil berkomunikasi dengan suami tentang cara mencegah kematian ibu pada ibu hamil risiko tinggi dan komunikasi interpersional baik dengan pengetahuan cukup sebanyak 23 responden (22,3%) hal ini terjadi kerena ibu hamil berkomunikasi dengan petugas kesehatan dan keder kesehatan tentang cara mencegah kematian ibu pada ibu hamil risiko tinggi. 9,10,11,12 Hasil uji analisis chi squere penelitian ini menunjukkan bahwa hubungan komunikasi interpersional dengan pengetahuan ibu hamil risiko tinggi (p=0,001), pada tingkatan komunikasi interpersional yang berarti <0,05 maka tidak ada hubungan komunikasi interpersionel dengan pengetahuan ibu hamil risiko tinggi.…”
Section: Pendahuluanunclassified
“…Kehamilan dengan resiko tinggi adalah kehamilan yang dapat menimbulkan dampak pada ibu hamil dan bayi menjadi sakit dan bahkan meninggal sebelum kelahiran terjadi (Indrawati, 2016). Aspek pemicu resiko kehamilan harus segera ditangani karena dapat mengancam keselamatan ibu, bahkan dapat terjadi kematian pada ibu dan bayi.…”
Section: Pendahuluanunclassified
“…Promosi kesehatan tentang kehamilan risiko tinggi dapat diberikan oleh tenaga kesehatan sebagai upaya mencegah bahaya lebih lanjut yang disebabkan oleh kehamilan risiko tinggi. Melalui peningkatan pengetahuan diharapkan dapat membawa perubahan perilaku kesehatan pada ibu maupun keluarganya (Indrawati et al, 2016…”
Section: Hasil Dan Pembahasanunclassified